2013
DOI: 10.1083/jcb.201210099
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BubR1 acetylation causes defects in spindle assembly checkpoint signaling and promotes tumor formation

Abstract: Failure of chromosome–spindle attachment and a weakened spindle assembly checkpoint lead to genetic instability and cancer in mice expressing acetylation-deficient BubR1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 49 publications
(94 reference statements)
6
73
0
Order By: Relevance
“…Lysine (K) 250 and 688 on BubR1 have been identified as the potential deacetylation targets of Sirt2 in human cells (North et al., 2014; Suematsu et al., 2014), which are corresponding to K243 and K657 residues in mice (Park et al., 2013). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysine (K) 250 and 688 on BubR1 have been identified as the potential deacetylation targets of Sirt2 in human cells (North et al., 2014; Suematsu et al., 2014), which are corresponding to K243 and K657 residues in mice (Park et al., 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Chromosome segregation in cells expressing BubR1‐K250Q was delayed, whereas mitotic progression was accelerated in cells expressing BubR1‐K250R (Choi et al., 2009). Loss of BubR1 acetylation causes defects in SAC signaling and promotes tumor formation in mice (Park et al., 2013). Recently, North et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data provide substantial evidence that the acetylation status of survivin is critical for genomic stability during mitosis. However, we are mindful that acetylation of other mitotic proteins including aurora-B 25 and BubR1 itself, 23 as well as certain cytokinetic proteins, may contribute to and exacerbate the mitotic and cytokinetic abnormalities seen in the chemically-induced acetylated state. In addition to mitotic defects we found that mimicking acetylation of survivin leads to some relocation to the nucleus, which concurs with Wang et al, (2010b).…”
Section: Discussionmentioning
confidence: 99%
“…For example, depletion of the ubiquitous and highly conserved HDAC3 prevents proper construction of the mitotic spindle and weakens kinetochore-microtubule attachment in prometaphase cells. 22 Furthermore many mitotic proteins, including tubulin, BubR1, 23 APC, shuogoshin-2, 24 CPPs aurora-B kinase 25 and survivin 6 are acetylated. Using acetylation mimetics, Wang et al, (2010) demonstrated that survivin acetylation at K129 influences its subcellular localization in interphase cells.…”
Section: Discussionmentioning
confidence: 99%